2014
DOI: 10.1530/rep-14-0126
|View full text |Cite
|
Sign up to set email alerts
|

Maternal age effect on mouse oocytes: new biological insight from proteomic analysis

Abstract: The long-standing view of 'immortal germline vs mortal soma' poses a fundamental question in biology concerning how oocytes age in molecular terms. A mainstream hypothesis is that maternal ageing of oocytes has its roots in gene transcription. Investigating the proteins resulting from mRNA translation would reveal how far the levels of functionally available proteins correlate with mRNAs and would offer novel insights into the changes oocytes undergo during maternal ageing. Gene ontology (GO) semantic analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
71
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(75 citation statements)
references
References 62 publications
2
71
0
Order By: Relevance
“…However, under some conditions (i.e., aging or disease) the genome defensive system becomes vulnerable due to loss of function, reduced expression level or misregulation of proteins important for genome maintenance. For example, decreased transcripts of SAC components Bub1 and Mad2 and reduced levels of cohesin proteins were observed during normative aging in oocytes (Schwarzer et al, 2014; Steuerwald et al, 2001; Tsutsumi et al, 2014), which might be related to the increased aneuploidy with age in these cells. Gene expression analysis of murine tissues previously shown to undergo age-related aneuploidization (Baker et al, 2013; Faggioli et al, 2012) revealed age-associated down-regulation of proteins important for chromosome segregation, such as components of the SAC and centromere proteins (Zahn et al, 2007)(Fig.…”
Section: Gin At the Chromosomal Level: Routes To Aneuploidy And Pomentioning
confidence: 99%
“…However, under some conditions (i.e., aging or disease) the genome defensive system becomes vulnerable due to loss of function, reduced expression level or misregulation of proteins important for genome maintenance. For example, decreased transcripts of SAC components Bub1 and Mad2 and reduced levels of cohesin proteins were observed during normative aging in oocytes (Schwarzer et al, 2014; Steuerwald et al, 2001; Tsutsumi et al, 2014), which might be related to the increased aneuploidy with age in these cells. Gene expression analysis of murine tissues previously shown to undergo age-related aneuploidization (Baker et al, 2013; Faggioli et al, 2012) revealed age-associated down-regulation of proteins important for chromosome segregation, such as components of the SAC and centromere proteins (Zahn et al, 2007)(Fig.…”
Section: Gin At the Chromosomal Level: Routes To Aneuploidy And Pomentioning
confidence: 99%
“…In addition, mouse oocyte aging changes the mRNA and protein expression. Dysfunctions of the aged ovary may be responsible for the changes . For maintenance of DNA methylation, DNMT1 is expressed in mouse oocytes, but its defect disturbs the expression of imprinted genes during early embryonic development .…”
Section: Characteristics Of Oocyte Agingmentioning
confidence: 99%
“…One mechanism involved in the etiology of increased aneuploidy with advanced maternal age is decreased levels of the cohesin proteins [ 31 ]. Therefore, investigators created genetic mouse models to mimic this decrease and answer specifi c questions about the roles of cohesin proteins during meiosis.…”
Section: Spindle Structure and Cohesin Proteinsmentioning
confidence: 99%